THE ROLE OF STOCK PRICES IN MODERATING THE INFLUENCE OF PROFITABILITY, SOLVENCY, AND FIRM SIZE TO FIRM VALUE IN CONSUMER GOODS INDUSTRY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) 2015-2020 PERIOD - Rida Aulia Novi Arisanty; Feri Dwi Riyanto (JURNAL EKBIS, 2022)
This study aims to analyze the effect of profitability, solvency, and firm size on firm value with stock price as a moderating variable. This research was conducted on consumer goods industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. The number of samples in this study was determined by purposive sampling method so that the number of samples that met the criteria were 26 companies. The type of data used is secondary data obtained through www.idx.co.id. The data analysis method used is Panel Data Regression with the Moderated Regression Analysis (MRA) test using the Eviews 10 software application. The results show that profitability has a\ positive and significant effect on firm value, solvency has a positive and significant effect on firm value, and firm size has negative and significant effect on firm value, stock prices are able to moderate the relationship between profitability, solvency, and firm size on firm value.